2015
DOI: 10.1007/s10854-015-3111-3
|View full text |Cite
|
Sign up to set email alerts
|

Citric sol–gel synthesis and luminescence characteristics of Ca1−y Sr y La2−x Eu x ZnO5 phosphors

Abstract: The emission-tunable CaLa 2-x Eu x ZnO 5 phosphors were synthesized by citric sol-gel method. The products were characterized by X-ray diffractometer, scanning electron microscope, energy dispersive spectroscopy and photoluminescence spectrometer. Through adjusting the dopant concentration of Eu 3? in CaLa 2 ZnO 5 phosphor, blue-green to orange-red emission with the 467 nm excitation could be obtained, which matches well with the emission of blue LED chip. Luminescence properties of Ca 1-y Sr y La 1.9 Eu 0.1 Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
101
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(106 citation statements)
references
References 28 publications
(24 reference statements)
5
101
0
Order By: Relevance
“…This is quite likely due to the enhanced magnetization in the nanocomposite sample of BFO-CZCF. This sort of behavior is also observed in other cases, 45,62 where the magnetization has been enhanced. BFO-CZCF exhibits the dispersion at low frequencies with a sharp variation of the permittivity and dielectric loss.…”
Section: Dielectric Propertiessupporting
confidence: 74%
“…This is quite likely due to the enhanced magnetization in the nanocomposite sample of BFO-CZCF. This sort of behavior is also observed in other cases, 45,62 where the magnetization has been enhanced. BFO-CZCF exhibits the dispersion at low frequencies with a sharp variation of the permittivity and dielectric loss.…”
Section: Dielectric Propertiessupporting
confidence: 74%
“…This observation is in agreement with other reports on Al, Mo, and Cr-doped HMS. [6][7][8]10 Liu et al 9 however, reported a contrast observation for chromium-doped polycrystalline HMS prepared by ball milling and in-situ SPS, but were not able to explain the reason for this unusual behavior. Comparison with chromium as dopant is because of the lack of a similar investigation for molybdenum and tungsten, all of which belong to the same group in the periodic table.…”
Section: Resultsmentioning
confidence: 95%
“…They adopt Nowotny chimney-ladder structures whose unit cells consist of Mn sublattices arranged as chimneys in which the Si sublattices form coupled helices spiraling as ladders. 1 A variety of work has been conducted on tuning the transport properties of HMS by substitution or doping, [4][5][6][7][8][9][10][11][12][13][14] compositing, [15][16][17] and nanostructuring. 18,19 For substitution at Si sites, the highest ZT values obtained were 0.6 at 833 K and 0.65 at 850 K for Ge and Al-doped polycrystalline HMS, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Partial substitution of Mn 3+ by Ni 2+ ions in manganites synthesized by solid state reaction (grain sizes ∼1 µm), has previously been studied in connection with the magnetoresistive behavior. 14,15 The dimensionality strongly impacts the magnetic and magnetocaloric response of LCMO. 9,16 In the present work, results of a study of the MCE on LCMO manganites, synthesized by auto-combustion method and substituted at the Mn site by Ni 2+ are presented.…”
Section: Introductionmentioning
confidence: 99%